2017
DOI: 10.1002/adfm.201604671
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumor‐Targeted Upconversion Nanoparticle‐Based Micelles for Simultaneous NIR‐Controlled Combination Chemotherapy and Photodynamic Therapy, and Fluorescence Imaging

Abstract: Although neuroendocrine tumors (NETs) are slow growing, they are frequently metastatic at the time of discovery and no longer amenable to curative surgery, emphasizing the need for the development of other treatments. In this study, multifunctional upconversion nanoparticle (UCNP)-based theranostic micelles are developed for NET-targeted and near-infrared (NIR)-controlled combination chemotherapy and photodynamic therapy (PDT), and bioimaging. The theranostic micelle is formed by individual UCNP functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 80 publications
1
113
0
1
Order By: Relevance
“…We and others have previously demonstrated that a rapid release of anticancer drugs within the tumor sites can lead to superior anticancer efficacies. 3235 In this work, the temperature elevation generated by the CuS NP core under NIR light induced both the PTT effect and the hydrophobic-to-hydrophilic phase transition of PAAmAN, leading to a rapid drug release, thereby achieving NIR-controlled combination chemotherapy and PTT. We tested these CuS-based micelles in triple-negative breast cancer (TNBC) models.…”
Section: Introductionmentioning
confidence: 82%
“…We and others have previously demonstrated that a rapid release of anticancer drugs within the tumor sites can lead to superior anticancer efficacies. 3235 In this work, the temperature elevation generated by the CuS NP core under NIR light induced both the PTT effect and the hydrophobic-to-hydrophilic phase transition of PAAmAN, leading to a rapid drug release, thereby achieving NIR-controlled combination chemotherapy and PTT. We tested these CuS-based micelles in triple-negative breast cancer (TNBC) models.…”
Section: Introductionmentioning
confidence: 82%
“…Amine-functionalized NaYF 4 :Yb/Tm/Er UCNPs (NH 2 -UCNPs) were prepared using a thermal decomposition method following the same protocol we previously reported [30], which was then converted to β-CD functionalized UCNPs (CD-UCNPs) through amidization. The average size of the CD-UCNPs determined by transmission electron microscopy (TEM) was 15 nm in diameter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The amine-functionalized UCNPs (NH 2 -UCNPs) were first prepared following the same protocol using a thermal decomposition method as published previously [30]. CD-UCNPs were then synthesized through amidization between NH 2 -UCNP and carboxymethyl-β-cyclodextrin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NPs can greatly enhance the stability and cellular uptake of the siRNA molecules [15,16]. Furthermore, NPs are attractive for targeted cancer therapy due to their passive (attributed to the enhanced permeability and retention (EPR) effect) and active (via specific ligand conjugation) tumor-targeting abilities [17,18]. However, in order to achieve high gene silencing efficiency, once the NPs are taken up by the target cancer cells, efficient siRNA escape from the acidic endosome/lysosome compartments and efficient siRNA decomplexation from its carrier in the cytosol are essential [6,1922].…”
Section: Introductionmentioning
confidence: 99%